2016
DOI: 10.1021/acsami.6b04816
|View full text |Cite
|
Sign up to set email alerts
|

Designing 3D Multihierarchical Heteronanostructures for High-Performance On-Chip Hybrid Supercapacitors: Poly(3,4-(ethylenedioxy)thiophene)-Coated Diamond/Silicon Nanowire Electrodes in an Aprotic Ionic Liquid

Abstract: A versatile and robust hierarchically multifunctionalized nanostructured material made of poly(3,4-(ethylenedioxy)thiophene) (PEDOT)-coated diamond@silicon nanowires has been demonstrated to be an excellent capacitive electrode for supercapacitor devices. Thus, the electrochemical deposition of nanometric PEDOT films on diamond-coated silicon nanowire (SiNW) electrodes using N-methyl-N-propylpyrrolidinium bis((trifluoromethyl)sulfonyl)imide ionic liquid displayed a specific capacitance value of 140 F g(-1) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 53 publications
1
39
1
Order By: Relevance
“…Such enhancement of the capacitance is similar or even better than those reported by using other porous carbon materials. [16] Second, the inferior behavior of the PC at high scan rates or current densities can be attributed to kinetically unfavorable diffusion of ions inside the narrow pores because of slow Na + ionic motion and low conductivity of the electrolyte, leading to loss of the full contribution of active surface area of a CNFs film.…”
Section: Performance Of Cnfs/bdd Ecs Capacitancementioning
confidence: 99%
See 1 more Smart Citation
“…Such enhancement of the capacitance is similar or even better than those reported by using other porous carbon materials. [16] Second, the inferior behavior of the PC at high scan rates or current densities can be attributed to kinetically unfavorable diffusion of ions inside the narrow pores because of slow Na + ionic motion and low conductivity of the electrolyte, leading to loss of the full contribution of active surface area of a CNFs film.…”
Section: Performance Of Cnfs/bdd Ecs Capacitancementioning
confidence: 99%
“…Such a process is automatically controlled by a single-board microcontroller which is also possible to be connected with a USB connector to a computer ( Figure 6a). [2] , diamond network (network) [3] , diamond/silicon nanowires (SiNW) [4] , diamond foam (Foam) [5] , honeycomb diamond (Honeycomb) [6] , porous diamond (Porous) [7] , BDD/Nanotube (Nanotube) [8] , BDD/carbon fiber (CF) [9] , BDD/'black silicon' (bSi) [10] , nitrogen included ultrananocrystalline diamond (N-UNCD) [11] , diamond paper (Paper) [12] , CNFs/BDD (CNF, this [14] , MnO 2 /BDD (MnO 2 ) [2] , Ni(OH) 2 /Diamond Nanowire (Ni(OH) 2 ) [15] , poly(3,4-(ethylenedioxy)thiophene)-coated diamond@silicon nanowires (PEDOT) [16] ; BDD based PC using redox electrolyte (Dia) [3a] , diamond network PC using redox electrolyte (Network) [3a] , CNFs/BDD PC using redox electrolyte (CNF, this work). [18] Cross-linked N-doped CNF network 1.0M H 2 SO 4 5.9 10.0 [19] Mesoporous CNF 6.0 M KOH 5.1 16.0 [20] CNF paper 6.0 M KOH 7.1 9.0 [21] Porous CNF composites 6.0 M KOH 17.0 20.0 [22] Porous CNF 1.0 M H 2 SO 4 ~6.0 20.0 [23] CNFs/BDD [24] ZnO/porous activated CNF 6.0 M KOH 22.7 4.0 [25] MnO 2 /CNF // CNF 0.5 M Na 2 SO 4 36 4.4 [26] CNFs/BDD …”
Section: Battery-like Supercapacitor Demonstratormentioning
confidence: 99%
“…The bare PANI layer makes this composite a promising candidate for supercapacitor applications. Aradilla et al . used silicon nanowires (50 μm long; 20–200 nm in diameter) grown by CVD as the substrate, which was covered by a diamond film, and finally a poly(3,4‐ethylenedioxythiophene) (PEDOT) layer.…”
Section: Diamond‐based Compositesmentioning
confidence: 99%
“…Both chemical reagents were used without further purification. The water content of ionic liquid was determined to be 42 ppm according to our previous work [16].…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…EMIM TFSI (1 M) À PC] were addressed to SiNW-based symmetric MSCs [15], demonstrating the potential of such strategy for doped silicon nanostructures in the field of supercapacitors. Therefore, in this work, we present for the first time a complete and exhaustive electrochemical study focused on a new electrolyte mixture (PC-N 1114 TFSI) to be employed as electrolyte in EDL MSC made of SiNW electrodes able to operate at a wide operating temperature range (0 to 80 C) within a large cell voltage of 3.5 V. The choice of employing N 1114 TFSI as electrolyte for the mixture of this study is ascribed to its excellent performance reported in our previous work dealing with SiNWs for supercapacitor devices [16] and its potential also for battery applications [17,18]. Additionally, ammonium structurebased ionic liquids have already demonstrated their enormous potential as electrolytes for carbon supercapacitors [19].…”
Section: Introductionmentioning
confidence: 99%